1998
DOI: 10.1210/jcem.83.7.4967
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of Insulin-Like Growth Factor (IGF)-I and -II in Iliac Crest Bone Matrix from Pre- and Postmenopausal Women: Relationship to Age, Menopause, Bone Turnover, Bone Volume, and Circulating IGFs1

Abstract: Insulin-like growth factor-I (IGF-I) and -II are important local regulators of bone metabolism, but their role as determinants of human bone mass is still unclear. In the present study, we analyzed the concentration of IGF-I and -II in the bone matrix of 533 human biopsies from the iliac crest that were obtained during surgery for early breast cancer. There was an inverse association of bone matrix IGF-I concentration with age that was unaffected by menopause. Bone matrix IGF-I was positively associated with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Specifically-although this was not the hypothesis of this work-we showed that utilizing bone chips, bone marrow, or a combination of both was associated with superior bone volume compared to bone marrow alone. This is in line with previous literature (Laubach et al, 2023a) where the bone matrix is host to various growth factors such as insulin-like growth factor 1 (Seck et al, 1998), bone morphogenetic protein (BMP)-2 and BMP-4 (Sipe et al, 2004;Dimitriou et al, 2005;Pecina and Vukicevic, 2007), and transforming growth factor-ß1 (Perez et al, 2018) that are deeply embedded in the bone matrix and thus sustainably released over time as the matrix is degraded and remodeled (Canalis et al, 1988;Joyce et al, 1990). Such controlled release of growth factors is not possible with bone marrow, which is rapidly resorbed by the body, thus limiting sustained bone regeneration.…”
Section: Discussionsupporting
confidence: 92%
“…Specifically-although this was not the hypothesis of this work-we showed that utilizing bone chips, bone marrow, or a combination of both was associated with superior bone volume compared to bone marrow alone. This is in line with previous literature (Laubach et al, 2023a) where the bone matrix is host to various growth factors such as insulin-like growth factor 1 (Seck et al, 1998), bone morphogenetic protein (BMP)-2 and BMP-4 (Sipe et al, 2004;Dimitriou et al, 2005;Pecina and Vukicevic, 2007), and transforming growth factor-ß1 (Perez et al, 2018) that are deeply embedded in the bone matrix and thus sustainably released over time as the matrix is degraded and remodeled (Canalis et al, 1988;Joyce et al, 1990). Such controlled release of growth factors is not possible with bone marrow, which is rapidly resorbed by the body, thus limiting sustained bone regeneration.…”
Section: Discussionsupporting
confidence: 92%
“…IGF-1 is the most abundant growth factor deposited in the bone ECM. 212 Osteocytes in particular secrete large amounts of IGF1, which is incorporated in the bone matrix. 213 Since IGF-1 is produced under loading, it might contribute to the mechanotransduction process.…”
Section: Osteoclastsmentioning
confidence: 99%
“…Therefore, it has a significant predictive value as a standard for the risk of osteoporosis and incident fractures. [13][14][15] Recently, another star molecule that has been found to be closely associated with the state of bone turnover is leptin. Adipocytes are critical components involved in modulating energy expenditure and bone cell activities.…”
Section: Introductionmentioning
confidence: 99%